Study of awareness of contraception in postnatal women - Rokade, Jyoti Vikas; Hanji, Vinutha R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was undertaken to know the awareness of contraception in postnatal women in a Government Hospital in Maharashtra. Methods: Authors conducted a prospective study in Department of Obstetrics and Gynecology at Government hospital, Miraj between January 2015 to September 2016. All postnatal patients in this hospital, willing to participate in the study were included in the study after a thorough written informed consent. Patients were given pre decided questions for answering. Answers were noted, counselling was done. Results: Out of 4860 women, 97% of the women were aware of at least 1 contraceptive method, the highest being of female sterilization (91%) 20.8% of women had ever used the contraception before and most of them used it in between pregnancies (64.4%). 79.2% had not used any contraception before and main reason for not using was found to be, they wanted to conceive (46%) followed by fear of side effects (24.7%) Regarding willingness to use the contraception after counselling, 48.5% of women said they were not sure. Among rest 51.4% women, female sterilization (32.4%) was preferred method followed by copper-T (22.8%) The most common source of information was by media and books which was 39.3%. Conclusions: There is a large lacuna between the awareness and practice of contraception. Proper education of both partners, increasing female literacy, socio economic upliftment, effective health care system is needed.